Testing the validity of two putative sympatric species from Sinocyclocheilus (Cypriniformes: Cyprinidae) based on mitochondrial cytochrome b sequences - Chen, Yan-Yan; Li, Rong; Li, Chun-Qing; Li, Wei-Xian; Yang, Hong-Fu; Xiao, Heng; Chen, Shan-Yuan (Zootaxa, 2018)
There are over 60 species within the freshwater fish genus Sinocyclocheilus (Cypriniformes: Cyprinidae) distributed throughout the Yunnan-Guizhou Plateau and its surrounding areas in China. In recent years, the increasing number of new species described has raised some controversy about the validity of several species within this genus, notably the putative sympatric species pair S. qiubeiensis and S. jiuchengensis. To test the validity of S. qiubeiensis and S. jiuchengensis, we analyzed the complete sequences of the mitochondrial cytochrome b (CYTB) gene of 20 identified species and one outgroup species. Phylogenetic relationships were reconstructed using CYTB with maximum likelihood (ML) and Bayesian inference (BI) methods. Our phylogenetic results showed that all individuals of S. qiubeiensis and S. jiuchengensis clustered in one clade with strong support. In addition, the genetic distance between the two species was 0.11%, within the range observed at the intraspecific level. The most recent common ancestor of S. qiubeiensis and S. jiuchengensis dated back to 0.13 million years ago, indicating little time for complete speciation to have occurred. These results clearly support the viewpoint that S. jiuchengensis is a synonym of S. qiubeiensis.